Reflections on Accidental Testimonies and Spectacular Witnesses - Lavinia Hirsu (Journal of the Assembly for Expanded Perspectives on Learning, 2012)
When unplanned-for testimonies occur in class, how do instructors turn a disruptive moment into a teachable one?